The Application of the STEM Approach in Mathematics Learning to Improve Critical Thinking Skills in Junior High School Students - Istian, Nova Sri (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the effectiveness of the STEM (Science, Technology, Engineering, and Mathematics) approach in improving junior high school students’ critical thinking skills in mathematics. The STEM approach emphasizes the integration of cross-disciplinary concepts through contextual projects that encourage students to think creatively, reflectively, and analytically. The research employed a quasi-experimental method with a non-equivalent control group design. The sample consisted of 64 eighth-grade students from a public junior high school in East Java. The results indicate that STEM-based instruction significantly enhances students’ critical thinking skills. These findings reinforce that STEM integration is effective for implementing 21st-century mathematics learning.